Pitfalls in diagnosis with the use of circulating tumor‐derived epidermal growth factor receptor mutations in lung cancer harboring pretreatment T790M. Issue 1 (24th October 2017) - Ogawara, Daiki; Soda, Hiroshi; Suyama, Takayuki; Yoshida, Masataka; Harada, Tatsuhiko; Fukuda, Yuichi; Mukae, Hiroshi
Abstract : The circulating tumor DNA (ctDNA) assay has recently been approved for the selection of EGFR‐tyrosine kinase inhibitors as first‐line treatment in lung cancer. However, it remains to be determined whether this assay can detect all complex EGFR mutations within a single tumor. We report a case of an elderly woman with stage IV lung adenocarcinoma, in which EGFR mutation assays detected L858R and pretreatment T790M from a tissue biopsy. In contrast, the circulating tumor DNA assay detected L858R, but not pretreatment T790M in the plasma, regardless of the fact that similar amounts of each mutation were present in the biopsy specimen. Treatment with afatinib was not effective, but subsequent treatment with osimertinib remarkably regressed the tumor. Our findings indicate that physicians should accurately evaluate EGFR‐tyrosine kinase inhibitor‐insensitive mutations using tissue samples in the first‐line setting, even when L858R and exon 19 deletions are detected in the plasma.